Derivations of gamma (semi)hyperrings - Ardekani, L. K.; Davvaz, B. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
Differential $Γ$ -(semi)hyperrings are $Γ$ -(semi)hyperrings equipped with derivation, which is a linear unary function satisfyingthe Leibniz product rule.We introduce the notions of derivation and weak derivation on $Γ$ -hyperrings and $Γ$ -semihyperringsand obtain some important results relating to them in a specific way.